Implementasi Metode Audiolingual Dalam Meningkatkan Mufrodat Pada Mata Pelajaran Bahasa Arab Kelas X Di MI.Miftaahul Huda Depok - Nafisatun Nadhifah; Siska Putri Sayekti (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2023)
The results of observations and interviews conducted by researchers at MI. Miftahul Huda Depok showed that the lack of completion of KKM 60 Arabic subjects among students led to low student Arabic learning outcomes because students had difficulty understanding Arabic learning. due to lack of knowledge of Arabic, who do not understand the importance of learning Arabic. The method used can increase the child's willingness to listen or understand when learning Arabic, because through visual observation the purpose of this research is to find out the application of the sound method in learning Arabic. The method used is classroom action research PTK. This research was conducted on 5th grade students, totaling 24 students. This survey was conducted by memorizing learning outcomes, filling out observation sheets, analyzing data with calculations described in the form of presentations based on children's learning outcomes. with the auditory speech method. Cycle 1 and Cycle 2 experienced an increase of 87%.